PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR IPA DITINJAU DARI MINAT BELAJAR - Aini, Eni Nur; Partono, Partono; Riswanto, Riswanto; Prihandono, Eko (Universitas Muhammadiyah Metro, 2021)
Abstract: The guided inquiry learning model is a model that involves all students' ability to search and investigate in a systematic, critical, logical, analytical and developing emotional and student skill. The purpose of this research is to know the difference of student learning outcomes between the control class and the experimental class after using the model guided inquiry learning and to know interest in learning to support the improvement of student learning outcomes. This type of research is a quasi experiment because not all variables can be managed and controlled strictly or fully. Where population in this research is all class of student of class VII SMPN 1 Pekalongan which amount 6 class. Sampling of this study researchers using purposive sampling, purposive sampling is a technique of determining the sample with certain considerations. The researcher used purposive sampling technique because the population is hoterogen. The sample used in this research is the students of class VII 1 and VII 2, which will be the control class and the experimental class. Data collection using questionnaires and tests. Questionnaires are used to determine students' learning interests and tests are used to determine student learning outcomes. Then the data can be further analyzed using anakova test.Keywords: Guided Inquiry Learning Model, Interest in Learning, and Learning Outcomes.